INFLUENCE STUDY OF REFRACTORY GOLD ORES BENEFICIATION BY FLOTATION PROCESS PARAMETERS: REVIEW - Hasurungan Tambunan, Yosafat
Gold is the most precious metal since it has limited availability and high value. Gold ores are divided into free milling ores and refractory gold ores. Nowadays, the invention of free milling ores has been declining and refractory gold ores is more likely to be found. As gold reserves also decreases, optimalization of refractory gold ores processing is needed. In this literature study, influence of several processing parameters in refractory gold ores flotation are reviewed. Literature sources are reviewed from science journals, books, reports and proceedings. These references are acquired by searching on the internet with gold ore, gold flotation, and refractory gold ores flotation as the specific keywords. Then, 51 literature sources are collected and reviewed. Percent of solids, agitation speed, particle size fraction, pulp pH, types and dosage of collector, and dosage of CuSO4 activator are the specific refractory gold ores flotation process parameters which are discussed in this study. Gold grades and recovery flotation statistics are shown on every parameter. Later on, the datas are analyzed and discussed to give conclusions that explain the literature review’s objectives along with the recommendation for future purposes. The result of literature review shows that greater pulp density will increase gold recovery in a range of 10-33%. Gold grades will increase as pulp density increases in a range of 25-35%. Coarser particle size requires faster minimum agitation speed. Faster agitation speed will increase gold recovery in a range of 900-1500 rpm. Largest gold grades is obtained at agitation speed in a range of 1200-1500 rpm. The influence of particle size fractions shows that gold recovery increases as particle size becomes finer in a range of -300+20 ?m. Gold grades increases as particle size become finer in a range of -300+74 ?m. The effect of pulp pH shows that gold recovery will increase as pH is raised from its natural value in a range of 7-8.5 to critical pH in a range of 8-11.1. In flotation with butyl xanthate (BX) as the collector, pulp pH in a range of 7-7.5 has larger gold grades compared with pulp with 8.5-9 pH. Influence of collector types shows that longer carbon chain collectors have better collecting ability towards sulphide mineral, while shorter carbon chain collectors have better selectivity. Sodium isoamyl xanthate (SIX) and potassium amyl xanthate (PAX) is the superior collectors to obtain higher recovery in sulphide gold ores flotation, while BX is used to get better gold grades. To achieve optimum recovery, xanthate collectors with shorter carbon chain requires more dosages compared to longer chain xanthate collectors. Gold grades increases at higher BX dosage in a range of 50-250 g/t and at higher SIX dosage in a range of 30-120 g/t. CuSO4 activator works better before PAX conditioning. In a range of 0-100 g/t, larger dosage of CuSO4 will result in higher sulphide gold recovery, but with lower grades. The optimum condition in refractory gold ores flotation is 33-35% pulp density, agitation speed of 1350-1500 rpm, particle size fractions of -105+20 ?m, pulp pH of 8-11.1, dosages at 100-120 g/t of SIX, PAX with dosages at 50-100 g/t, BX with dosages at 180-350 g/t, and activator CuSO4 with dosages at 100 g/t.